Health beliefs about hypertension among hypertensive elderly people in Khammam urban locality: health belief model - Veerapu, Nagapraveen; Kumar Baer, Philip Ravi; Kudumula, Meghana (International Journal Of Community Medicine And Public Health, 2020)
Background: Increased globalization, urbanization, improvements in science and technology, information technology made life style changes; prone to increased risk of non communicable diseases. Beliefs about hypertension determine behaviour of the hypertensive people towards hypertension and its complications. Health beliefs about hypertension can be studied by health belief model. The objectives were to know the socio-demographic characteristics and to quantify the health beliefs among elderly hypertensive people in the light of Health belief model. Methods: A cross sectional study was done for a period of 6 months from January 2018 to June 2018 among people aged 50 years and above who were hypertensives in Khammam urban locality. Randomly 160 people were selected for the study. Data was collected by using a semi-structured questionnaire. Analysis will be done using proportions. Results: The average number of years the individuals known to have hypertension was 6.38 years. The current systolic blood pressure in most of the elderly was in between 140-149 mm of Hg. The current diastolic BP in most of the elderly was 81-90 mm of Hg was followed by less than 80 mm of Hg. In the study, health beliefs were quantified. More than half of elderly had perceived threat of hypertension (54.6%). The health beliefs of perceived benefits were 44%. Perceived threats of barriers were 62.7%. Conclusions: The information obtained will be useful for planning the health education or health promotion programs based on the needs and deficiencies of the people.